Empowering the Rural Communities through Education on the Use of Chrysanthemums as Medicinal Plants and Herbal Tea - Tia Setiawati; Annisa Annisa; Mohamad Nurzaman; Rusdi Hasan; Nining Ratningsih (Universitas Serang Raya, 2023)
Chrysanthemum is widely known as ornamental plants, but chrysanthemums can also be used as medicinal plants and can be processed into healthy beverages known as chrysanthemum tea. The purpose of the PPM activity is to educate the community, especially PKK women who are participants in this activity about the role of chrysanthemum plants in the prevention and treatment of various diseases such as fever, hypertension, osteoporosis, eye healthy and making chrysanthemum tea as a healthy beverage. PPM activities was carried out through outreach activities with presentations and discussions (question and answer), demonstrations of making chrysanthemum tea, and distributing questionnaires to determine participants understanding before and after the implementation of PPM activities. The results of the questionnaire showed that participants knowledge about the use of chrysanthemum as medicinal ingredients increased after participating in outreach activities, as well as the interest in chrysanthemum tea cultivation and entrepreneurship.